Modeling the major influencing factor on match running performance during the in-season phase in a Portuguese professional football team - Teixeira, José Eduardo (2022)
The aim of this study was two-fold: (1) to analyze the influence of season phase (i.e., the start of the in-season and mid-in-season) on match running performance in a Portuguese professional football team; (2) to determine and model the main factor influencing match running performance during the in-season in this specific football team. Eighteen matches were collected by an 18 Hz global positioning system (GPS) from a professional Portuguese football team during the start of the in-season and mid-in-season. The match running performance was analyzed according to season phases, presenting significant differences in total distance (TD) (tlower bound = 4.71, p < 0.001; tupper bound = −2.22, p = 0.002), average speed (AvS) (tlower bound = 359.45, p < 0.001; tupper bound = −359.87, p < 0.001), and relative high speed running (rHSR) (tlower bound = 13.10, p < 0.001; tupper bound = −10.21, p < 0.001). The logistic regression showed TD (β = −1.59, z = −2.84, p = 0.005) and AvS (β = 2.68, z = −2.84, p = 0.007) as the major factors influencing match running performance during seasonal variation. Sprints and accelerations showed no significance for predicting match running performance during the season phases (β = −0.05 to 1.07, z = −0.95 to 1.07, p = 0.29 to 0.72). Current research confirms that lower and upper bounds should be used to quantify seasonal differences on match running performance. TD and AvS were described as the main factors influencing match running performance during the in-season phase. Thus, it is important to highlight the pace and volume of the game to maximize match running performance.